Developing an OBE-Based Paragraph Writing E-Module to Improve Writing Skills - Budiarta, I Komang; Kumara, Dewa Gede Agung Gana; Murtini, Ni Made Wersi (JOLLT Journal of Languages and Language Teaching, 2026)
Innovation in education is essential, and higher education likewise undergoes a comparable phenomenon. The limited availability of learning materials and access to them for the Paragraph Writing course remained a challenge. It encourages lecturers to innovate and create optimal learning quality, and modules can facilitate students’ independent and flexible learning. Lecturers are expected to develop innovative and interactive learning modules, such as an E-Module. The current research aims to develop a Paragraph Writing E-Module based on the OBE curriculum and assess its quality. This research used an R&D design. To collect the data, the researchers employed document analysis, structured questionnaires, and semi-structured interviews. The collected data were then analyzed quantitatively and qualitatively. The E-Module has been developed according to the ADDIE stages, incorporating the results of the target and learning needs analysis. Besides, inputs from validators regarding design, content, and language have been followed up on. The E-Module trial results pointed out that students can follow it easily and flexibly, starting from understanding concepts and practicing writing, and so do lecturers. The design has been made as attractive as possible, and the learning materials are arranged to help students easily understand the material. Technology is incorporated to enhance interactivity, hence facilitating autonomous improvement of comprehension and writing skills. To sum up, the researcher determined that the Paragraph Writing E-Module is very viable as instructional material for the Paragraph Writing course. Additionally, it has been developed to align with the OBE curriculum, which can be applied to other language courses.